Physiothreapeutic treatments in infants with congenital hip dysplasia - Edyta Piechocka; Bartłomiej Wrzesiński; Paweł Wojtczak; Anna Ziółkowska; Dominika Ciecierska (Kazimierz Wielki University, 2018)
Congenital dysplasia is the most common congenital orthopaedic defect in children. Its occurrence is estimated at 2-4% of newborns (1:400), where majority of cases concern girls (85%). This disease was observed in greater numbers in people living in Central, Southern, Eastern Europe and the Sami people. This distortion may be caused by genetic and mechanical factors or incorrect prophylaxis during childcare processes. Treatment depends on the degree of damage, the age of the child and the speed of diagnosing the disease. Surgical, conservative and prophylactic treatment is used, and in each one of these physiotherapy plays and important role. Physiotherapy in the treatment of hip joints is used in form of kinesiotherapy, massage and the selection of appropriate orthopedic equipment to correct the defect and maintain the therapeutic effect obtained during surgical treatment. It also allows and helps in maintaining proper function of limbs.